2013
DOI: 10.1007/s13762-013-0400-3
|View full text |Cite
|
Sign up to set email alerts
|

Microbe assisted phytoremediation of oil sludge and role of amendments: a mesocosm study

Abstract: A mesocosm study was evaluated to elucidate the influence of amendments such as microbial consortium, plant (Vetiveria zizanioides), bulking agent (wheat husk) and nutrients on remediation of oil sludge over a period of 90 days. The experiment was conducted in a 15 m 2 plot which was divided into eight units comprising of soil sludge mixture (1:1) at CSIR-NEERI premises. During the experiment, oil degradation was estimated gravimetrically and polyaromatic hydrocarbons (PAHs) were quantified on GC-MS. Additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Nanekar et al [57] proved that adding extra microorganisms (bioaugmentation) to the soil contaminated with petroleum-derived compounds decreased the amount of total petroleum hydrocarbons (TPH) in the soil, and also resulted in lowering the lead, cadmium, and zinc content while increasing manganese content. Most often, these results coincide with the outcome of our experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Nanekar et al [57] proved that adding extra microorganisms (bioaugmentation) to the soil contaminated with petroleum-derived compounds decreased the amount of total petroleum hydrocarbons (TPH) in the soil, and also resulted in lowering the lead, cadmium, and zinc content while increasing manganese content. Most often, these results coincide with the outcome of our experiment.…”
Section: Resultsmentioning
confidence: 99%
“…However, there were no significant differences (P < 0.05) between the compost and vermicompost amendment on the removal of total ash-PAHs. The higher PAH removal in PCA and PVA treatments than in other treatments indicated that the maize plants could stimulate the growth and activity of soil autochthonous microorganism involved in PAH degradation due to the production of exudates released in maize rhizosphere as was reported by Nanekar et al (2015). Moreover, the compost or vermicompost used together with maize could stimulate the activity of soil autochthonous PAH degraders which could be supported by PAH degraders augmented to soil from the amendments.…”
mentioning
confidence: 60%
“…It majorly covers several remedial technologies which enhance biodegradation of the contaminant by supplementing soils with growth substrates/co-substrates. The most common biostimulation agents include bulking agents, nutrient supplementation, halogenated priming compounds (halo-priming), and surfactants (Passatore et al 2014; Nanekar et al 2015). The rate of PCB dechlorination can be increased by priming with halogenated compound.…”
Section: Biostimulation Of Aerobic Organismsmentioning
confidence: 99%